Helicobacter pylori infection in gastric carcinoma in the Van region of Turkey - M. Kürşat TÜRKDOĞAN; Süleyman ALICI; Mahmut İLHAN and Hüsniye DİLEK and Emel AKMAN and Hayati AYAKTA and Metin KARAKÖK (Turkish Journal of Gastroenterology, 2019)
-